The Effect of Self-Efficacy on Teachers’ Organizational Citizenship Behavior: A Case of MTsN 1 Mataram City - Badrun, Badrun; Bahtiar, Bahtiar; Maimun, Maimun (FKIP Universitas Lampung, 2022)
The Effect of Self-Efficacy on Teacher’s Organizational Citizenship Behavior at MTsN 1 Mataram City. Objectives: This study aims to determine the effect of self-efficacy on the Organizational Citizenship Behavior of teachers at MTsN 1 Mataram City. Methods: This research was conducted at MTsN 1 Mataram City teachers as many as 62 people. The sampling technique is popular. The data collection technique used is the distribution of questionnaires. Data analysis using simple linear regression and t-test. Self-efficacy indicators consist of magnitude, generality, and strength. Indicators of Organizational Citizenship Behavior are Altruism, Conscientiousness, Sportsmanship, Courtesy, and Civic Virtue. Findings: The results of the simple regression test showed that the significance value was less than 0.05. The results of the t-test also show that the t-count value of 3.830 is greater than the t-count value of 1.685. Conclusion: This indicates that there is a significant influence between self-efficacy and the Organizational Citizenship Behavior of teachers at MTsN 1 Mataram City. Keywords: self-efficacy, organizational citizenship behavior.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202227